A sui generis purification: The national and international consequences of the expulsion of General Vaccaro from the IOC - Sbetti, Nicola (Hispania Nova, 2019)
This article analyzes the purification process that the world of sports in Italy experienced after the Second World War. In particular, the research focuses on the case study of Giorgo Vaccaro, who during the fascist period held various positions in the world of sports, such as the president of the Italian Football Federation (FIGC), general secretary of the Italian Olympic Committee (CONI) and member of the International Olympic Committee (IOC). During the postwar period, Vaccaro was the only one of the three Italian IOC members who was expelled from this organization supposedly because of his fascist past and despite the fact that most of the sports directors during fascism were reinstated in their posts. In reality, behind his expulsion there was a clear power struggle within the CONI that spanned from 1948 to 1950, which highlights the importance of the historical study of international relations between sports organizations. This research has used for its elaboration records of the CONI and IOS´ archives.